Flouting Conversational Maxims In The Rom-Com Movie The Kissing Booth 2 - Dohans, Western; Ayomi, Putu Nur (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
To create effective communication, individuals must adhere to the four conversational maxims or principles of cooperation. However, in the world of movies, language use tends to be more varied, and sometimes not subject to the norms of language politeness and the context of language use. As a result, the information conveyed can be unclear and ambiguous, which in turn leads to violations of the conversational maxims. The purpose of this study is to analyze the types of flouting maxims found in The Kissing Booth 2 Movie and to identify the reasons behind the flouting maxim since it is very important to make communication as effective as possible. In this study, the researcher used a theory proposed by Grice in Levinson in analyzing the types of flouting maxims and the theory proposed by Leech in analyzing the reason behind the flouting maxim that occurs in the movie. This study used a descriptive qualitative method to provide a deeper understanding of the flouting maxim and the reasons for flouting. The data were collected from the conversations that occurred among the characters in The Kissing Booth 2 Movie. The results found that there were violations of the maxims of quantity, quality, relevance, and manner committed by the characters. Relevance violations are less frequent (8.3%) and typically occur when characters fail to shift topics in response to specific questions. Intriguingly, maxim violations do not invariably yield negative outcomes, as characters collaborate to convey their intended meanings smoothly. This collaborative approach is particularly prevalent (65%), signifying that characters often flout maxims when illocutionary goals diverge from social goals. Ultimately, the study concludes that the flouting maxim of quantity prevails, and collaborative reasons dominate as the most common motivation behind maxim deviations.